The land of the elephant kings: space, territory, and ideology in the Seleucid Empire - Kosmin, Paul J. (Harvard Univ. Press, 2014)
Part I. Border -- India: diplomacy and ethnography at the Mauryan frontier -- Central Asia: nomads, ocean, and the desire for line -- Part II. Homeland -- Macedonia: from center to periphery -- Syria: diasporic imperialism -- Interlude: the Kingdom of Asia -- Part III. Movement -- Arrivals and departures -- The circulatory system -- Part IV. Colony -- King makes city -- City makes king